Hypoechoic liver in fetuses with trisomy 21. (2nd October 2019) - Omar, Puspa Marlinda; Lim, Wan Teng; Ting, Yuen Ha; Lao, Terence T.; Law, Kwok Ming; Cheung, Alvin Ho Kwan; Ng, Joanna Ka Man; Leung, Tak Yeung
Abstract: The association between hypoechoic hepatomegaly in the third trimester and transient abnormal myelopoiesis (TAM) was reported previously in six fetuses with trisomy 21 (T21). We report a series of three cases of T21 in which hypoechoic liver (HL) was found in the second trimester but without evidence of TAM on both hematological and histological examination. We postulate that the hypo-echogenicity may be due to liver congestion secondary to hemodynamic disturbances seen in T21 fetuses. All three cases had negative first trimester Down syndrome screening and one case was detected solely because of the isolated finding of HL. HL per se may be associated with T21 and more positive cases are required to support this association.